Longley, Edna. Yeats and Modern Poetry. Modernism Against the Grain - Mateus, Andréa Martins Lameirão (ABEI Journal, 2014)
Longley, Edna. Yeats and Modern Poetry. Cambridge University Press, 2013. 268 pp.